2016
DOI: 10.1128/jb.00480-15
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Cyclic Di-AMP to the Staphylococcus aureus Sensor Kinase KdpD Occurs via the Universal Stress Protein Domain and Downregulates the Expression of the Kdp Potassium Transporter

Abstract: Nucleotide signaling molecules are important intracellular messengers that regulate a wide range of biological functions. The human pathogen Staphylococcus aureus produces the signaling nucleotide cyclic di-AMP (c-di-AMP). This molecule is common among Gram-positive bacteria and in many organisms is essential for survival under standard laboratory growth conditions. In this study, we investigated the interaction of c-di-AMP with the S. aureus KdpD protein. The sensor kinase KdpD forms a two-component signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
120
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(124 citation statements)
references
References 71 publications
4
120
0
Order By: Relevance
“…These include expelling cytoplasmic protons through the F 1 F 0 -ATPase, producing alkaline compounds to neutralize the cytoplasmic pH, and importing osmolytes such as choline or proline (46, 47). Microarray data from S. aureus cultured in medium acidified to pH 4.5 revealed that besides genes encoding urease and proton efflux pumps, oxidative stress response genes and the kdp and opuC operons, encoding the c-di-AMP receptor proteins KdpD and OpuCA, are up-regulated (45, 4851). Although an intriguing correlation, understanding the mechanism through which elevated c-di-AMP levels contributes to the acid tolerance in S. aureus or other microorganisms awaits future studies.…”
Section: Discussionmentioning
confidence: 99%
“…These include expelling cytoplasmic protons through the F 1 F 0 -ATPase, producing alkaline compounds to neutralize the cytoplasmic pH, and importing osmolytes such as choline or proline (46, 47). Microarray data from S. aureus cultured in medium acidified to pH 4.5 revealed that besides genes encoding urease and proton efflux pumps, oxidative stress response genes and the kdp and opuC operons, encoding the c-di-AMP receptor proteins KdpD and OpuCA, are up-regulated (45, 4851). Although an intriguing correlation, understanding the mechanism through which elevated c-di-AMP levels contributes to the acid tolerance in S. aureus or other microorganisms awaits future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of c-di-AMP in the major human pathogen S. aureus has been limited to mediating ion homeostasis by regulating channel activity (11,36,37). In this study, we investigated an extracellular role for c-di-AMP during S. aureus biofilm growth and regulation of macrophage activation and functional activity.…”
Section: Discussionmentioning
confidence: 99%
“…(29,30). Cytosolic c-di-AMP is sensed by both the endoplasmic reticulum resident protein stimulator of interferon genes (STING) (31-33) and the helicase DDX41 (34); however, the individual contributions of these proteins in sensing c-di-AMP remain unclear.While several intracellular proteins function as c-di-AMP receptors in S. aureus (11,(35)(36)(37)(38), the spatial and temporal production as well as any extracellular role for c-di-AMP during biofilm development has yet to be determined. Furthermore, the ability of extracellular c-di-AMP to trigger type I IFN production in macrophages has not yet been demonstrated and may serve as a potential mechanism to polarize macrophages to an anti-inflammatory state characteristic of biofilm infections (3,(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…C-di-AMP has been shown to bind to the RCK_C domain of another S. aureus transporter, the cation-proton antiporter CpaA, and to the KdpD sensor histidine kinase, which typically controls the expression of another potassium uptake system, as well as several virulence factors in the pathogen 18,19 .…”
Section: Membrane Transport and Ion Homeostasismentioning
confidence: 99%
“…Interestingly, c-di-AMP can be both essential, which makes it unique among second messengers, and toxic, when overproduced 1214 . Similarly to c-di-GMP, c-di-AMP controls a spectrum of cellular processes, including gene expression 15 , DNA repair 11 , cell wall synthesis 16 , metabolism 17 and potassium homeostasis (Figure 2) 12,18,19 .…”
Section: Introductionmentioning
confidence: 99%